Evaluation of CRP SNV rs2808630 and acute proinflammatory biomarkers in patients with CKD and PLHIV with CKD: a case-control study - Andrea Torres-Rojas; Luz Alicia González-Hernández; Karina Sánchez-Reyes; Jonathan Samuel Chávez-Iñiguez; Jorge Fernando Topete-Reyes; Jaime Federico Andrade-Villanueva; Pedro Martínez-Ayala; Adriana Valle-Rodriguez; Vida Verónica Ruiz-Herrera; Jorge Hernández-Bello; Zyanya Reyes-Castillo; Monserrat Álvarez-Zavala (BMC Nephrology)
Abstract Background The CKD in PLHIV is highly prevalent in Jalisco. Despite its control with ART, HIV is characterized by generating low-grade inflammation events that contribute to the development and progression of CKD. Considering the importance of hs-CRP in the context of CKD, various genetic predisposition studies have been conducted to search for variants of the CRP gene, among which the SNV rs2808630 has been associated with serum hs-CRP concentrations and progression of CKD. Due to the above, there is interest in studying this SNV, addressing the limited information available on this topic in Mexico. Methods The case-control study included 163 patients with CKD, 102 PLHIV with CKD under ART with undetectable viral loads from the Hospital Civil of Guadalajara “Fray Antonio Alcalde” and 115 controls. Clinical assessment and general laboratory studies were carried out. Also, serum quantification of inflammatory biomarkers was performed by ELISA method. The determination of CRP SNV rs2808630 by qPCR and the association with inflammatory biomarkers was evaluated. Statistical analysis was carried out considering significant values p < 0.05. Results Lower prevalence of CC genotype was shown in our population. Of the 358 samples, 221 (61.7%) present the wild-type genotype. The results analyzed correspond with what has been reported worldwide in studies of CRP SNV rs2808630 in the development of CKD without having a relationship with inflammatory and kidney function biomarkers. However, higher creatinine and IL-6 concentrations were observed in the group with the CC genotype. A significant correlation between IL-6 and eGFR was identified in CKD patients, but not for PLHIV with CKD, highlighting a potential difference in inflammatory dynamics between these groups. Importantly, in PLHIV with CKD, we found a strong correlation between hs-CRP and IL-8, suggesting a possible association with a higher proportion of the inflammatory isoform of hs-CRP, which may have implications for disease progression and cardiovascular risk. Conclusions The presence of the CRP SNV does not appear to contribute to the development of CKD and has no association with inflammatory biomarkers. Though, genetically independent manner, hs-CRP levels are slightly different between groups and are underrated when related to the CKD stage in PLHIV. Also, high IL-6 concentrations are related to CKD progression, while IL-8 seems to have a better relation to CKD in PLHIV.